OVERVIEW OF METHODS AND TOOLS FOR DRYING WALNUTS IN THE SHELL - RUTKEVYCH, Volodymyr; DIDYK, Andrii (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The question of increasing the quality indicators of walnut in the process of storage and processing, due to the use of modern and progressive methods and means for its drying, is considered.It is noted that Ukraine has a significant potential in the cultivation of walnuts, but due to the lack of modern and highly efficient means for its processing, it is forced to sell them at low prices as raw materials to secondary markets. The increased moisture content of walnuts during harvesting at the level of 35-45% and the lack of modern highly efficient and energy-saving equipment in Ukraine leads to the storage of this product in natural conditions in specially covered and well-ventilated rooms. This process of drying the fruits is very long, since excess moisture constantly acts on the walnuts, creating conditions for the active development of microorganisms. When it rains, this method of drying often leads to complete spoilage of the fruits. Therefore, for highly efficient business related to walnuts, special drying equipment is simply indispensable. This equipment will help to significantly speed up the process, make it more efficient and economically profitable, and will allow to bring the moisture content of the walnut to the International Standard (no more than 10%) and technical requirements.It has been established that modern methods and means for drying prevent the appearance of mold, ensure high quality of valuable nut kernels and guarantee a long shelf life. Fresh nuts are dried to a residual moisture content of 6-12% in a stream of dry warm air at a temperature of 20 to 36 °C. The drying temperature of a walnut depends on its size and humidity. The drying process can be carried out both in professional drying cabinets and with the help of special heating devices for drying nuts.Modern efficient drying equipment from the time-tested brands Feucht-Obsttechnik, Amb Rousset and other companies were considered. The new highly efficient and resource-saving equipment is presented in the form of sectional structures, which works on an economical gas heat generator. In this equipment, whole nuts are dried for 1-3 days, as a result of which the humidity reaches 12-13 %. The productivity of such equipment, depending on the number of sections, is 1-4 tons of products per day.It is also stated that among the variety of existing technologies and means of drying raw materials, the most promising ways to intensify the process while ensuring high quality of the finished product and increasing production efficiency are devices that combine different modes and methods of drying.
Keywords: walnut; drying equipment; productivity; energy efficiency; costs; humidity